ChemInform Abstract: Construction of Indoloquinolinones via Pd(II)‐Catalyzed Tandem C—C/C—N Bond Formation: Application to the Total Synthesis of Isocryptolepine. Issue 18 (May 2015) - Chen, Xuebing; Sun, Peng; Xu, Jinyi; Wu, Xiaoming; Kong, Lingyi; Yao, Hequan; Lin, Aijun
Abstract The Pd‐catalyzed reaction of indole‐3‐carboxamides with aryl iodides affords indoloquinolinones in moderate yields.